DEVELOPING ENGLISH TEACHING MATERIALS FOR YOUNG LEARNERS BASED ON ISLAMIC VALUES OF INTEGRATED LANGUAGE SKILLS FOR ISLAMIC ELEMENTARY SCHOOL - Savitri . Rahmadany; Rahmad . Husein; Masitowarni . Siregar (Universitas Negeri Medan, 2021)
ABSTRACT This Research and Development (R&D) is conducted to develop English teaching materials for young learners of grade four based on Islamic values of integrated language skills at SD IT AL Hijrah 2 Deli Serdang. The objectives of this study are 1) to analyze English teaching materials are needed by the students, 2) to develop the English teaching materials, and 3) to give reasons for the English teaching materials developed. The respondent of this study is 23 respondents which consisted of twenty (20) fourth-grade students, one (1) English teacher, and two (2) lecturers. The data is collected by questionnaire, interview, and documentary. The results of this study showed that 1) English teaching materials needed by the students are English teaching materials based on Islamic values of integrated language skills, 2) the development of English teaching materials were developed through four steps, namely evaluation and need analysis, material development, material validation, and revision and final product, and 3) the reason English teaching materials are developed based on Islamic values of integrated language skills is because of the Islamic elementary schools and the terms or level of young learners. Based on the expert’s judgment result, the score was 3.68, and the percentage is 90% categorized as very good. It means that the developed materials were relevant or appropriate for the fourth-grade students of Islamic elementary school. It implies that the teacher can use the developed English teaching materials based on Islamic values of integrated language skills and Islamic elementary needs to lead the students to learn English in the Islamic context. Keywords: Research and Development (R&D), Teaching Materials for Young Learners, Islamic Values of Integrated Language Skills, Islamic Elementary School